Consumer tastes towards buying several types of drinks at the Simple coffee shop (a case study of consumers at the “Simple” coffee shop, Surabaya) - Wiyasa, I Gede (International Conference On Economics Business Management And Accounting (ICOEMA), 2022)
In the city of Surabaya, there are already many coffee shops that can be found with almost the same products and prices. For this reason, coffee shop owners must be able to provide something or implement business strategies, such as conducting a SWOT analysis to develop long-term strategies so that business directions and goals can be achieved clearly and can immediately take the right decisions in dealing with competitors and can provide value added and different from competitors.. The formulation of the problem in this study is to describe consumer behavior in purchasing several types of drinks at a simple coffee shop. The research method used in making this journal is a comparative approach or can be called the comparative approach method with primary data collection through random sampling technique. The place of research was carried out at the “simple” coffee shop Raya Deles, Surabaya. The results of this study were that more coffee drink products were purchased from several other types of drinks with a total of 164 cups, then followed by 131 glasses of drinks, 83 glasses of ginger drink, and finally 58 glasses of red ginger.